The factors of demographic risk in social insurance of the selected European Union countries - Balcerowicz-Szkutnik, Maria; Szkutnik, Włodzimierz (Czynniki ryzyka demograficznego w ubezpieczeniach społecznych wybranych państw Unii Europejskiej, 2010)
Of the study its presents the forecasts for value of selected demographic measures, obtained from the forecasts of population age structure, elaborated by national statistical offices and available as a part of EUROSTAT base. This is the next version of forecasts worked out by the authors of the study – the previous ones were achieved with the method of arithmethic mean, harmonic wights as well as trend function determined on the basis of time series for years 1991 to 2006. Due to the fact that there are no ideal forecasts, there are only more or less accuarate forecasts, it pays to use the next possibility to determine them for the same measures. It gives the chance to compare forecasts and choose the best ones. The following part of the study focuses on the forecasts for value of coefficients that determine the scale of ageing process. The EU countries selected for comparative analyses include these from the group of countries newly joining the EU, ie. The countries which pose a peculiar mystery for the union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 106, s. 11-20